Oceanic storm surges in the outer Mackenzie Delta, NWT Canada: Remote Sensing of tundra disturbance and restoration from saline intrusion - LAPKA, STEPHANIE (Graduate Studies, 2013)
As the Circumpolar Arctic continues to undergo strong environmental change - such as increased annual temperatures and decreased sea ice cover - natural disturbances are occurring at frequencies and magnitudes never before recorded (Chapin et al. 2000; Manson and Solomon 2007; Shaver and Kummerow 1992). Coastlines and low-lying terrain have been predicted to be among the environments most susceptible to disturbance events, especially within the western Canadian Arctic (Forbes 2011; Lantuit et al. 2011). In September 1999, an oceanic storm surge occurred over the alluvial islands of the outer Mackenzie Delta, NWT Canada. The salt water incursion killed more than 250 km2 of freshwater tundra. Over a decade later, dead vegetation remains the dominant land cover for more than one quarter of the impacted region. Dynamic retrospective studies such as the one conducted here are important tools for properly monitoring current processes and forecasting future impacts within Arctic landscapes (Hilbert 2006). Landsat imagery has provided the data needed to perform an ecological assessment distinctive from almost all vegetation-based studies conducted within the Circumpolar Arctic to date. Completed within this thesis is a land cover map time series with close to annual coverage between 1972 and 2010 of the alluvial islands in the outer Mackenzie Delta, as well as the first landscape-level vegetation recovery assessment of the area from the largest oceanic storm surge event to have occurred there in the past 1,000 years.